Reliability‐based hull geometry optimisation of a point‐absorber wave energy converter with power take‐off structural reliability objectives - Anna Garcia‐Teruel; Caitlyn E. Clark (IET Renewable Power Generation, 2021)
Abstract Recent studies have focused on optimising wave energy converter (WEC) designs, maximising their power performance and techno‐economic feasibility. Reliability has yet to be fully considered in these formulations, despite its impact on cost and performance. In this study, this gap is addressed by developing a reliability‐based design optimisation framework for WEC hull geometries to explore the trade‐off between power performance and power take‐off (PTO) system damage equivalent loading (DEL). Optimised hull geometries for two sites are considered (from the centre of the North Sea and off the west coast of Norway), and two directions of motions (heave and surge). Results indicate that site characteristics affect the potential power production and DEL for an optimal WEC design. These are also affected by the direction of motion for power extraction, which also significantly changes optimal hull shape characteristics. Optimal surging WEC designs have edges facing oncoming wave directions, while heaving WECs have pointed bottoms, both to streamline movement. Larger, more convex WECs result in greater power production and DEL, while smaller, more concave WECs result in lesser power production and DEL. These findings underline the importance of considering WEC hull geometry in early design processes to optimise cost, power production, and reliability.